Assessing the impact of screening, early identification and intervention programmes for chronic kidney disease: protocol for a scoping review - Ikechi G. Okpechi; Fergus Caskey; Abduzhappar Gaipov; Elliot Koranteng Tannor; Laura Hamonic; Gloria Ashuntantang; Jo‐Ann Donner; Ana Elizabeth Figueiredo; Reiko Inagi; Magdalena Madero; Charu Malik; Monica Moorthy; et al. (BMJ, 2021)
Chronic kidney disease (CKD) is a major threat to public health, especially in low-income and lower middle-income countries, where resources for treating patients with advanced CKD are scarce. Although early CKD identification and intervention hold promise for reducing the burden of CKD and risk factors, it remains unclear if an uniform strategy can be applicable across all income groups. The aim of this scoping review is to synthesise available evidence on early CKD identification programmes in all world regions and income groups. The study will also identify efforts that have been made to use interventions and implementation of early identification programmes for CKD across countries and income groups. This review will be guided by the methodological framework for conducting scoping studies developed by Arksey and O'Malley. Empirical (Medline, Embase, Cochrane Library, CINAHL, ISI Web of Science and PsycINFO) and grey literature references will be searched to identify studies on CKD screening, early identification and interventions across all populations. Two reviewers will independently screen references in consecutive stages of title/abstract screening and then full-text screening. We will use a general descriptive overview, tabular summaries and content analysis on extracted data. The findings from our planned scoping review will enable us to identify items in early identification programmes that can be used in developing screening toolkits for CKD. We will disseminate our findings using traditional approaches that include open-access peer-reviewed publication, scientific presentations and a white paper (call to action) report. Ethical approval will not be required for this scoping review as the data will be extracted from already published studies.